Behavior of mixtures asphalt prepared with asphalts and wax modification (2013)
The main purposeof the research was to modify Colombian asphalts with natural waxes to produce warm asphalt mixes and establish its mechanical and dynamic behavior. The studied mixtures correspond to the curves sieved curves called md-10 and md-12 according to the classification of the Instituto de Desarrollo Urbano (IDU). The studystarted characterizingthe used materials(granular aggregate, asphalt andnatural waxes), and following by determining the optimum percentagesofwaxandasphalt contentadded to prepare mixes.Subsequently, it was prepared and compacted warm asphaltic mixes using temperatures at 110, 130 and 150 °C to evaluate the effect ofmodifiedasphaltin its mechanical and dynamicbehavior. The used tests to measure the asphalt mixtures propertieswereindirecttensile strength, preserve strength and resilientmoduliresistant. The results of the analysis presents that the used natural waxes reduce the viscosity of the asphalts and as a result of this the temperature of preparation and compaction of the mixes drops which highly decrease the energy consumption during the preparation process. Therefore the generated greenhouse effect gases are also reduced. Moreover, other observation reveals that the mechanical and dynamic properties in asphalts mixes are similar to the conventional mixes which allow very good chances for its practical applications.